Positive electrode material and preparation method thereof, positive plate and battery
By forming an oxygen halide and a carbon coating on the surface of high nickel ternary materials, the problem of degradation of safety performance of lithium-ion batteries under high temperature and high voltage is solved, and the effect of extending the thermal runaway time and reducing the thermal runaway temperature is achieved, and the circulation and safety performance of the battery is improved.
Patent Information
- Application Number
- CN202510134961.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-03-07
AI Technical Summary
The high-nickel ternary cathode material in existing lithium-ion batteries has reduced safety performance at high temperatures and high voltages, which can easily lead to thermal runaway and affect the cycling performance and safety of the battery.
By forming an oxygen halide and a carbon cladding layer on the surface of the high-nickel ternary material, the oxygen halide can react with the oxygen released by the high-nickel ternary material, endothermic heat reduction and increase the oxygen release temperature; the carbon cladding layer covers the oxygen halide to avoid its reaction with the electrolyte, and improve the stability and conductivity of the material.
It extends the time when the battery has thermal runaway, reduces the maximum temperature of thermal runaway, and improves the battery's circulation and safety performance.
Smart Images

Figure CN119569137A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet and a battery. Background Art
[0002] Lithium-ion batteries have achieved rapid development in the field of electric vehicles due to their high energy density, long cycle life, and environmental friendliness. With the application of ultra-high specific energy batteries with a cell specific energy of up to 360Wh / kg, the cruising range of electric vehicles has been greatly improved.
[0003] At present, although the battery cell has achieved high energy density, its safety performance is reduced because the positive and negative electrode materials in the battery cell are a combination of high-nickel ternary positive electrode material and silicon-carbon negative electrode material. Not only can it fail to pass the rigorous puncture test, but the maximum temperature of the battery when thermal runaway occurs can reach 1000°C. This is because the high-nickel ternary positive electrode material decomposes under high temperature and high voltage to produce oxygen. The oxygen reacts with the flammable organic electrolyte and the lithium-embedded negative electrode to release a large amount of heat, thus causing the battery to fail safely.
[0004] Therefore, how to optimize high-nickel ternary positive electrode materials to improve the safety performance of batteries is a technical problem that needs to be solved urgently. Summary of the invention
[0005] In view of this, the embodiments of the present application provide a positive electrode material and a preparation method thereof, a positive electrode sheet and a battery to solve at least one problem existing in the background technology.
[0006] In a first aspect, an embodiment of the present application provides a method for preparing a positive electrode material, the method comprising the following steps: S1: uniformly mixing a high-nickel ternary material and a metal halide, performing a first heat treatment under a first protective gas atmosphere to form an oxyhalide on the surface of the high-nickel ternary material, and after cooling, obtaining a ternary material with the oxyhalide coated on the surface; The molecular formula of the oxyhalide is Li a M b O c X d , wherein M includes at least one of Zr, Nb, Ta, W, Ti, La, Yb, In, Er, Sb, Sc, Y, Ho, Hf, Ga, and Dy, X includes at least one of Cl, Br, and I, 0.5≤a≤6, 0.1≤b≤10, 0.1≤c≤2, and 1≤d≤8; S2: uniformly mixing the ternary material coated with oxyhalide, a carbon source and a solvent, performing a second heat treatment under a second protective gas atmosphere to form a carbon coating layer on the surface of the ternary material coated with oxyhalide, and obtaining the positive electrode material after cooling.
[0007] In combination with the first aspect of the present application, in an optional implementation, the surface of the high-nickel ternary material includes residual alkali, and the oxyhalide is formed by the reaction of the residual alkali and the metal halide.
[0008] In conjunction with the first aspect of the present application, in an optional implementation manner, step S1 satisfies at least one of the following features: (1) The molecular formula of the high nickel ternary material is LiNi x Co y N z O2, wherein N includes at least one of Mn, Al, Mg, Zr, Ti, W, and B, 0.6≤x≤1.0, 0≤y≤0.2, and 0≤z≤0.4; (2) The metal halide includes at least one of TaCl5, NbCl5, ZrCl4, HfCl4, GaCl3, InCl3, ScCl3, YCl3, YbCl3, YBr3, and ErI3; (3) The mass ratio of the high nickel ternary material to the metal halide is 625:(1-12); (4) The first protective gas includes an inert gas; (5) The temperature of the first heat treatment is 250°C to 500°C; (6) The heating rate of the first heat treatment is 5°C / min~20°C / min; (7) The holding time of the first heat treatment is 4h~10h.
[0009] In conjunction with the first aspect of the present application, in an optional implementation manner, step S2 satisfies at least one of the following features: (1) The carbon source includes at least one of glucose, sucrose, citric acid, ascorbic acid, polyvinyl alcohol, phenolic resin, and starch; (2) The mass of the carbon source is 0.3% to 1.5% of the mass of the ternary material coated with oxyhalide; (3) The solvent includes a polar organic solvent; (4) The second protective gas includes an inert gas; (5) The temperature of the second heat treatment is 150°C to 400°C; (6) The heating rate of the second heat treatment is 5°C / min to 20°C / min; (7) The holding time of the second heat treatment is 4h~10h.
[0010] In a second aspect, an embodiment of the present application provides a positive electrode material, comprising a core and a first coating layer and a second coating layer sequentially coating the core; The core includes a high-nickel ternary material; the first coating layer includes an oxyhalide, the molecular formula of the oxyhalide is Li a M b O c X d , wherein M includes at least one of Zr, Nb, Ta, W, Ti, La, Yb, In, Er, Sb, Sc, Y, Ho, Hf, Ga, and Dy, X includes at least one of Cl, Br, and I, 0.5≤a≤6, 0.1≤b≤10, 0.1≤c≤2, and 1≤d≤8; and the second coating layer includes a carbon coating layer.
[0011] In conjunction with the second aspect of the present application, in an optional embodiment, the lithium in the oxyhalide is derived from the residual alkali on the surface of the high-nickel ternary material; and / or, The molecular formula of the high nickel ternary material is LiNi x Co y N z O2, wherein N includes at least one of Mn, Al, Mg, Zr, Ti, W, and B, 0.6≤x≤1, 0≤y≤0.2, and 0≤z≤0.4.
[0012] In conjunction with the second aspect of the present application, in an optional embodiment, the thickness of the first coating layer is 2nm~30nm; and / or, The thickness of the second coating layer is 1 nm to 16 nm.
[0013] In conjunction with the second aspect of the present application, in an optional implementation, the mass of the second coating layer is 0.3% to 1.5% of the sum of the masses of the core and the first coating layer.
[0014] In a third aspect, an embodiment of the present application provides a positive electrode sheet, comprising a positive electrode material prepared by the method for preparing a positive electrode material as described in any one of the first aspect or comprising the positive electrode material as described in any one of the second aspect.
[0015] In a fourth aspect, an embodiment of the present application provides a battery, comprising the positive electrode sheet described in the third aspect.
[0016] Compared with the prior art, the embodiments of the present application have the following beneficial effects: The positive electrode material and its preparation method, positive electrode sheet and battery provided in the embodiments of the present application, in the preparation method of the positive electrode material, an oxyhalide and a carbon coating layer are formed in sequence on the surface of the high-nickel ternary material, the oxyhalide can react with the oxygen released by the high-nickel ternary material, the reaction is endothermic, which can effectively reduce the heat generation and increase the oxygen release temperature of the high-nickel ternary material, thereby prolonging the time for the battery to experience thermal runaway and reducing the maximum temperature of thermal runaway, and the oxyhalide is stable under high voltage and has high lithium ion conductivity, which can improve the specific capacity of the positive electrode material; the carbon coating layer coats the oxyhalide, which can avoid the reaction of the oxyhalide with the electrolyte, thereby ensuring the stability of the oxyhalide, and the carbon coating layer can not only improve the electronic conductivity of the positive electrode material, but the carbon in the carbon coating layer can also react with the oxygen released by the high-nickel ternary material, thereby better avoiding the direct reaction of oxygen with the electrolyte to release heat, therefore, the positive electrode material prepared in the embodiments of the present application can better improve the cycle performance and safety performance of the battery.
[0017] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings: Figure 1 A schematic diagram of a process for preparing a positive electrode material provided in an embodiment of the present application; Figure 2 This is a schematic diagram of the structure of a high-nickel ternary material including residual alkali on the surface in an embodiment of the present application; Figure 3 A schematic diagram of the structure of the positive electrode material provided in the embodiment of the present application to form an oxyhalide during the preparation process; Figure 4 A schematic diagram of the structure of a positive electrode material provided in an embodiment of the present application. DETAILED DESCRIPTION
[0019] In order to make the technical scheme and beneficial effects of the present invention more obvious and easy to understand, the following is described in detail by combining the accompanying drawings and listing specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually based on conventional experimental conditions. The reagents and raw materials used in the present invention are commercially available unless otherwise specified.
[0020] In the following description, a large number of specific details are given to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features known in the art are not described; that is, all features of the actual embodiments are not described here, and well-known functions and steps are not described in detail.
[0021] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be limiting of the present application. When used herein, the singular forms "a", "an" and "said / the" are also intended to include plural forms, unless the context clearly indicates otherwise. The terms "consisting of" and / or "comprising", when used in this specification, determine the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.
[0022] In order to thoroughly understand the present application, detailed steps and detailed structures will be presented in the following description to illustrate the technical solution of the present application. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other implementation methods.
[0023] Unless otherwise defined, technical and scientific terms used in this application have the same meanings as those in the technical field to which this application belongs.
[0024] If no specific techniques or conditions are specified in the following examples, the conventional techniques or conditions described in the literature in the art, or the conditions recommended by the product instructions and the manufacturer are generally used. The numerical ranges in the following examples all include the endpoint values.
[0025] In order to solve the safety problem of batteries, some current research focuses on using non-flammable solid electrolytes to prepare solid-state batteries. However, due to factors such as poor ionic conductivity and high interface impedance in solid-state batteries, solid-state batteries are difficult to achieve large-scale application.
[0026] Based on this, the present invention provides a method for preparing a positive electrode material. Figure 1 The preparation method of the positive electrode material provided in the embodiment of the present application comprises the following steps: S1: Evenly mix the high nickel ternary material and the metal halide, perform a first heat treatment under a first protective gas atmosphere, form an oxyhalide on the surface of the high nickel ternary material, and after cooling, obtain a ternary material with the oxyhalide coated on the surface; the molecular formula of the oxyhalide is Li a Mb O c X d , wherein M includes at least one of Zr, Nb, Ta, W, Ti, La, Yb, In, Er, Sb, Sc, Y, Ho, Hf, Ga, and Dy, X includes at least one of Cl, Br, and I, 0.5≤a≤6, 0.1≤b≤10, 0.1≤c≤2, and 1≤d≤8; S2: Evenly mix the ternary material with the surface coated with oxyhalide, the carbon source and the solvent, perform a second heat treatment under a second protective gas atmosphere, form a carbon coating layer on the surface of the ternary material with the surface coated with oxyhalide, and obtain the positive electrode material after cooling.
[0027] In the embodiment of the present application, an oxyhalide (also referred to as a first coating layer) and a carbon coating layer (also referred to as a second coating layer) are sequentially formed on the surface of the high-nickel ternary material (also referred to as an inner core). The oxyhalide can react with the oxygen released by the high-nickel ternary material. The reaction is endothermic, which can effectively reduce the heat generation and increase the oxygen release temperature of the high-nickel ternary material, thereby prolonging the time for the battery to experience thermal runaway and reducing the maximum temperature of thermal runaway. In addition, the oxyhalide is stable at high voltage and has high lithium ion conductivity, which can improve the specific capacity of the positive electrode material. The carbon coating layer coats the oxyhalide, which can avoid the reaction of the oxyhalide with the electrolyte, thereby ensuring the stability of the oxyhalide. In addition, the carbon coating layer can not only improve the electronic conductivity of the positive electrode material, but the carbon in the carbon coating layer can also react with the oxygen released by the high-nickel ternary material, thereby better avoiding the direct reaction of oxygen with the electrolyte to release heat. Therefore, the positive electrode material prepared in the embodiment of the present application can better improve the cycle performance and safety performance of the battery.
[0028] The molecular formula of the high nickel ternary material in step S1 can be LiNi x Co y N z O2, wherein N includes at least one of Mn, Al, Mg, Zr, Ti, W, and B, 0.6≤x≤1.0, 0≤y≤0.2, and 0≤z≤0.4.
[0029] The metal halide in step S1 may include, for example, a transition metal halide. For example, the metal halide may include at least one of TaCl5, NbCl5, ZrCl4, HfCl4, GaCl3, InCl3, ScCl3, YCl3, YbCl3, YBr3, and ErI3.
[0030] During the preparation process of high-nickel ternary materials, excess lithium salt is usually added. The lithium salt is generally LiOH and / or Li2CO3. Therefore, a large amount of LiOH and / or Li2CO3 will remain on the surface of the high-nickel ternary material obtained after the reaction. The LiOH and / or Li2CO3 remaining on the surface of the high-nickel ternary material is called residual alkali.
[0031] In some embodiments, please refer to Figure 2 and Figure 3 , the surface of the high nickel ternary material 200 includes residual alkali 201 (please refer to Figure 2 ), the oxyhalide 210 is formed by the reaction of the residual base 201 with the metal halide. Figure 3 It can be seen that through the reaction between the residual alkali 201 on the surface of the high-nickel ternary material 200 and the metal halide, a relatively uniform and complete oxyhalide 210 can be formed on the surface of the high-nickel ternary material 200. Of course, in some other embodiments of the present application, the addition of lithium salt to form oxyhalide in step S1 is not excluded.
[0032] In the embodiment of the present application, oxyhalides are formed by the reaction of residual alkali and metal halide, so that oxyhalides can be generated without adding additional lithium salts, which not only reduces costs but also allows the oxyhalides to be more evenly and firmly coated on the surface of the high-nickel ternary material to form a denser and more complete oxyhalide coating layer, thereby further improving the stability of the oxyhalide coating layer under high voltage, and is also beneficial to improving the coating effect of the subsequently formed carbon coating layer on the oxyhalides.
[0033] It can be understood that the greater the mass of the high-nickel ternary material, the greater the amount of residual alkali on its surface. The amount of metal halide added in step S1 can be adjusted according to the mass of the high-nickel ternary material, so as to form a ternary material with a higher quality surface-coated oxyhalide. In some specific embodiments, the mass ratio of the high-nickel ternary material to the metal halide can be 625: (1~12), for example, it can be 625: 1, 625: 3, 625: 5, 625: 7, 625: 10, 625: 12 or any value between any two of the above numerical ranges. In this way, it can better ensure that the metal halide reacts fully with the residual alkali on the surface of the high-nickel ternary material, thereby forming a more uniform and complete oxyhalide coating layer, and at the same time, it can reduce the residual alkali content in the final positive electrode material as much as possible, thereby further improving the comprehensive performance of the positive electrode material.
[0034] In the actual preparation process, for example, the residual alkali content on the surface of the high-nickel ternary material can be first detected, and then the amount of metal halide required can be calculated based on the residual alkali content, wherein the residual alkali content on the surface of the high-nickel ternary material can be detected by a method well known to those skilled in the art. By using an appropriate amount of metal halide, the residual alkali on the surface of the high-nickel ternary material can be completely reacted to form an oxyhalide, so that the final cathode material no longer contains residual alkali, thereby further improving the performance of the final cathode material.
[0035] In the actual preparation process, the amount of metal halide added can also be determined by referring to the thickness of the oxyhalide coating layer to be formed. In some embodiments, the thickness of the oxyhalide formed in step S1 can be 2nm to 30nm.
[0036] There is no particular restriction on the type of the first protective gas in step S1, and it can be selected according to actual needs to protect the material during the first heat treatment. Exemplarily, the first protective gas may include an inert gas, such as at least one of argon, helium, and nitrogen.
[0037] In some embodiments, the temperature of the first heat treatment in step S1 can be 250°C to 500°C, for example, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, or any value between any two of the above ranges. In this way, while ensuring the formation of high-quality oxyhalides, it can avoid adverse effects on the composition and structure of the high-nickel ternary material, such as preventing the high-nickel ternary material from being reduced under high temperature conditions, thereby further improving the quality of the final cathode material.
[0038] In some embodiments, the heating rate of the first heat treatment may be 5°C / min to 20°C / min, for example, 5°C / min, 10°C / min, 15°C / min, 20°C / min, or any value between any two of the above ranges. In this way, the material can be heated more evenly in the first heat treatment, that is, the temperature distribution inside the material is more even, which is conducive to further improving the quality of the formed oxyhalide, thereby further improving the quality of the final cathode material.
[0039] In some embodiments, the holding time of the first heat treatment may be 4 h to 10 h, for example, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or any value between any two of the above ranges. This ensures that the reaction to form the oxyhalide is more fully carried out, thereby further improving the uniformity and integrity of the formed oxyhalide coating layer, which is beneficial to improving the quality of the final cathode material.
[0040] There is no particular restriction on the types of carbon source, solvent and second protective gas in step S2, and they can be selected according to actual needs. For example, the carbon source may include at least one of glucose, sucrose, citric acid, ascorbic acid, polyvinyl alcohol, phenolic resin, and starch. The solvent may include, for example, a polar organic solvent; further, the solvent may include organic alcohols, specifically, for example, at least one of methanol, ethanol, isopropanol, n-butanol, octanol, and decanol. The second protective gas may include, for example, an inert gas, specifically, for example, at least one of argon, helium, and nitrogen.
[0041] In step S2, the mass of the carbon source can be 0.3% to 1.5% of the mass of the ternary material coated with oxyhalide on the surface, for example, 0.3%, 0.5%, 0.7%, 0.9%, 1.0%, 1.2%, 1.5% or any value between any two of the above numerical ranges. This is conducive to improving the coating integrity of the carbon coating layer, while avoiding the thickness of the carbon coating layer being too thick, and can better ensure the coating effect of the formed carbon coating layer on the ternary material coated with oxyhalide on the surface, thereby further improving the comprehensive performance of the prepared positive electrode material.
[0042] The second heat treatment in step S2 can also be called carbonization treatment. When the temperature of the second heat treatment is too low, the conductivity of the formed carbon coating is relatively low; when the temperature of the second heat treatment is too high, it is easy to have an adverse effect on the structure of the ternary material with the surface coated with oxyhalide. Therefore, in some embodiments, the temperature of the second heat treatment in step S2 can be 150°C~400°C, for example, it can be 150°C, 200°C, 250°C, 300°C, 350°C, 400°C or any value between any two of the above numerical ranges. In this way, the formation of a high-quality carbon coating layer can be promoted, the conductivity of the carbon coating layer can be improved, and the coating effect of the carbon coating layer on the oxyhalide can be improved, while avoiding adverse effects on the structure of the material itself, thereby further improving the quality of the obtained positive electrode material.
[0043] In some embodiments, the heating rate of the second heat treatment in step S2 can be 5°C / min to 20°C / min, for example, 5°C / min, 10°C / min, 15°C / min, 20°C / min, or any value between any two of the above numerical ranges. In this way, the material can be heated more evenly in the second heat treatment, that is, the temperature distribution inside the material is more even, which is conducive to further improving the quality of the formed carbon coating layer, thereby further improving the quality of the prepared positive electrode material.
[0044] In some embodiments, the holding time of the second heat treatment in step S2 can be 4h~10h, for example, 4h, 5h, 6h, 7h, 8h, 9h, 10h or any value between any two of the above numerical ranges. In this way, the reaction of forming the carbon coating layer can be more fully carried out, thereby further improving the uniformity and integrity of the formed carbon coating layer, which is beneficial to improving the quality of the prepared positive electrode material.
[0045] The present application also provides a positive electrode material, such as Figure 4 As shown, the positive electrode material may include a core 100 and a first coating layer 110 and a second coating layer 120 that sequentially coat the core 100; the core 100 may include a high-nickel ternary material; the first coating layer 110 may include an oxyhalide, and the molecular formula of the oxyhalide may be Li a M b O c X d , wherein M includes at least one of Zr, Nb, Ta, W, Ti, La, Yb, In, Er, Sb, Sc, Y, Ho, Hf, Ga, and Dy, X may include at least one of Cl, Br, and I, 0.5≤a≤6, 0.1≤b≤10, 0.1≤c≤2, and 1≤d≤8; and the second coating layer 120 may include a carbon coating layer.
[0046] In the embodiment of the present application, the first coating layer 110 and the second coating layer 120 sequentially coat the core 100 including the high-nickel ternary material. The oxyhalide in the first coating layer 110 can react with the oxygen released by the high-nickel ternary material. The reaction is endothermic, which can effectively reduce the heat generation and increase the oxygen release temperature of the high-nickel ternary material, thereby extending the time for the battery to experience thermal runaway and reducing the maximum temperature of thermal runaway. In addition, the first coating layer 110 including the oxyhalide is stable at high voltage and has a high lithium ion conductivity, which can improve the positive electrode material. The second coating layer 120 covers the first coating layer 110, which can prevent the first coating layer 110 from reacting with the electrolyte, thereby ensuring the stability of the first coating layer 110. The second coating layer 120 includes a carbon coating layer, which can not only improve the electronic conductivity of the positive electrode material, but the carbon in the second coating layer 120 can also react with the oxygen released by the high-nickel ternary material, thereby better avoiding the direct reaction of oxygen with the electrolyte to release heat. Therefore, the positive electrode material in the embodiment of the present application can better improve the cycle performance and safety performance of the battery.
[0047] For example, the molecular formula of the high nickel ternary material can be LiNi x Co y N zO2, wherein N includes at least one of Mn, Al, Mg, Zr, Ti, W, and B, 0.6≤x≤1, 0≤y≤0.2, and 0≤z≤0.4. More specifically, x+y+z=1, that is, the molar number of Ni in the high-nickel ternary material accounts for more than 60% of the molar number of the total metal (including Ni, Co, and N).
[0048] In some embodiments, the lithium in the oxyhalide is derived from residual alkali on the surface of the high nickel ternary material.
[0049] In the embodiment of the present application, the oxyhalide in the first coating layer 110 can be generated with the help of the residual alkali on the surface of the high-nickel ternary material, that is, the residual alkali is used as the lithium salt to form the oxyhalide. In this way, the first coating layer 110 can be more evenly and firmly coated on the surface of the core 100, reducing costs, and can reduce or even remove the residual alkali on the surface of the high-nickel ternary material, thereby further improving the performance of the positive electrode material. Because, when there is too much residual alkali on the surface of the high-nickel ternary material, it will affect the processing performance of the positive electrode material, and the manufactured battery is prone to swelling when stored at high temperature, which will lead to a decrease in battery capacity and safety problems.
[0050] Furthermore, the lithium in the oxyhalide can all be derived from the residual alkali on the surface of the high-nickel ternary material. That is, in the actual preparation process of the first coating layer 110, no additional lithium salt is added, and the residual alkali is fully used as the lithium salt for forming the oxyhalide, which can further reduce the cost and further improve the performance of the positive electrode material.
[0051] It can be understood that when the thickness of the first coating layer 110 is too small, the core 100 may not be coated well and evenly, and the effect of improving the performance of the positive electrode material is small; when the thickness of the first coating layer 110 is too large, it is not conducive to the transmission of lithium ions and will increase the internal resistance of the battery. Therefore, in some specific embodiments, the thickness of the first coating layer 110 can be 2nm~30nm, for example, it can be 2nm, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm or any value between any two of the above numerical ranges. In this way, the gram capacity of the positive electrode material can be better improved, and the time for thermal runaway of the battery can be further extended. In the actual preparation process, the residual alkali on the surface of the high-nickel ternary material is used as a lithium salt to form an oxyhalide, which is also convenient for controlling the thickness of the first coating layer 110 within the above range.
[0052] It can be understood that when the thickness of the second coating layer 120 is too small, it is not conducive to more completely coating the first coating layer 110, and it is easy to cause the oxyhalide in the first coating layer 110 to react with the electrolyte, thereby affecting the performance of the positive electrode material; when the thickness of the second coating layer 120 is too large, it is not conducive to the transmission of lithium ions and will increase the internal resistance of the battery. Therefore, in some specific embodiments, the thickness of the second coating layer 120 can be 1nm~16nm, for example, it can be 1nm, 3nm, 5nm, 8nm, 10nm, 13nm, 16nm or any value between any two of the above numerical ranges. In this way, the performance of the positive electrode material can be further improved, thereby better improving the cycle performance and safety performance of the battery.
[0053] In some embodiments, the mass of the second coating layer 120 can be 0.3% to 1.5% of the sum of the mass of the core 100 and the first coating layer 110, for example, 0.3%, 0.5%, 0.7%, 1.0%, 1.2%, 1.5%, or any value between any two of the above numerical ranges. This is conducive to improving the coating integrity of the second coating layer 120, while avoiding the thickness of the second coating layer 120 being too thick, and can better ensure the coating effect of the second coating layer 120 on the first coating layer 110. Through the combination of the second coating layer 120 and the first coating layer 110, the comprehensive performance of the positive electrode material can be further improved, thereby further improving the comprehensive performance of the battery.
[0054] An embodiment of the present application further provides a positive electrode sheet, comprising the positive electrode material described in any of the above embodiments or a positive electrode material prepared by the method for preparing the positive electrode material described in any of the above embodiments.
[0055] It should be understood that the beneficial effects of the positive electrode material described in any of the above embodiments or the positive electrode material prepared by the method for preparing the positive electrode material described in any of the above embodiments are all applicable to the positive electrode sheet.
[0056] In some embodiments, the positive electrode sheet may include a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer may include the positive electrode material described in any of the above embodiments or the positive electrode material prepared by the preparation method of the positive electrode material described in any of the above embodiments. As an example, the positive electrode current collector has two surfaces opposite to each other in its own thickness direction, and the positive electrode active material layer may be disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0057] An embodiment of the present application further provides a battery, which includes the positive electrode sheet described in the above embodiment.
[0058] It should be understood that the beneficial effects of the positive electrode sheet in the above embodiments are all applicable to the battery.
[0059] In some embodiments, the battery may be a secondary battery, and the secondary battery may be a lithium-ion secondary battery. Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions, lithium ions, are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is disposed between the positive electrode sheet and the negative electrode sheet, and mainly plays the role of preventing the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0060] The technical solution of the present application is further described below in combination with a plurality of embodiments and comparative examples. Example 1
[0061] The preparation of the positive electrode material in this embodiment includes the following steps: Step S101: Take 5kg of high nickel ternary material (molecular formula is LiNi 0.83 Co 0.12 Mn 0.05 O2), add 16g of TaCl5 (metal halide), mix evenly for 10min, heat to 250℃ (wherein, the heating rate is 5℃ / min) in N2 atmosphere, keep warm for 4h (first heat treatment), and after sufficient reaction, naturally cool to room temperature, and use the residual alkali Li2CO3 and LiOH on the surface of the high-nickel ternary material to in-situ synthesize an oxyhalide coating layer (molecular formula is LiTaOCl4) on the surface of the high-nickel ternary material to obtain a ternary material with oxyhalide coated on the surface; wherein, the reaction of TaCl5 with Li2CO3 and LiOH is: TaCl5+Li2CO3→LiTaOCl4+LiCl+CO2, TaCl5+LiOH→LiTaOCl4+HCl; Step S102: Take 5 kg of the ternary material with surface coated oxygen halide obtained in step S101, mix it evenly with 500 g of a mixed solution of glucose and ethanol (wherein the mass fraction of glucose in the mixed solution is 5%), heat it to 400°C (wherein the heating rate is 10°C / min) under N2 atmosphere, and keep it warm for 6 hours (second heat treatment). After sufficient reaction, naturally cool it to room temperature to complete the carbon coating treatment, that is, form a carbon coating layer on the surface of the ternary material with surface coated oxygen halide to obtain a positive electrode material. Example 2
[0062] The preparation of the positive electrode material in this embodiment is basically the same as that in Embodiment 1, except that: 1) In step S101, the metal halide is replaced by NbCl5, and the molecular formula of the obtained oxyhalide is LiNbOCl4; wherein, the reaction of NbCl5 with Li2CO3 and LiOH is: NbCl5+Li2CO3→LiNbOCl4+LiCl+CO2, NbCl5+LiOH→LiNbOCl4+HCl.
[0063] 2) The temperature of the first heat treatment is 300°C. Example 3
[0064] The preparation of the positive electrode material in this embodiment is basically the same as that in Embodiment 1, except that: 1) In step S101, the metal halide is replaced by ZrCl4, and the molecular formula of the obtained oxyhalide is Li 1.75 ZrO 0.5 Cl 4.75 ; Among them, the reaction of ZrCl4 with Li2CO3 and LiOH is: ZrCl4+Li2CO3→Li 1.75 ZrO 0.5 Cl 4.75 +LiCl+CO2, ZrCl4+LiOH→LiNbOCl4+HCl.
[0065] 2) The temperature of the first heat treatment is 400°C.
[0066] Comparative Example 1 The positive electrode material in this comparative example directly adopts high nickel ternary material (molecular formula LiNi 0.83 Co 0.12 Mn 0.05 O2).
[0067] Comparative Example 2 The preparation of the positive electrode material in this comparative example has the same step S101 as that in Example 1, but omits step S102, that is, an oxyhalide coating layer is formed on the surface of the high-nickel ternary material, and no carbon coating layer is formed on the surface of the oxyhalide coating layer.
[0068] Comparative Example 3 The preparation of the positive electrode material in this comparative example is basically the same as that in Example 1, except that: 1) In step S101, the metal halide is replaced by TaF5, and the molecular formula of the obtained oxyhalide is LiTaOF4; wherein, the reaction of TaF5 with Li2CO3 and LiOH is: TaF5+Li2CO3→LiTaOF4+LiF+CO2, TaF5+LiOH→LiTaOF4+HF.
[0069] 2) The temperature of the first heat treatment is 300°C.
[0070] The positive electrode materials in the above embodiments and comparative examples were tested, and the specific tests are as follows: (1) Thickness test of coating layer Transmission electron microscopy (TEM) was used to characterize the thickness of the oxyhalide coating layer and the carbon coating layer in the cathode material.
[0071] (2) Differential Scanning Calorimetry (DSC) Test First, the positive electrode materials in the above-mentioned embodiments and comparative examples are prepared into batteries. Specifically, the positive electrode material, the conductive agent (conductive carbon black) and the binder (polyvinylidene fluoride, PVDF) are mixed in a mass ratio of 90:5:5, and the evenly mixed slurry is coated on an aluminum foil and dried. After rolling and cutting, the positive electrode sheet is obtained. The electrolyte is a solution of 1.15M LiPF6 dissolved in a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:7. The negative electrode is lithium metal with a thickness of 30μm, and the diaphragm adopts a composite diaphragm (7μm polyethylene + 3μm ceramic) with a total thickness of 10μm, and the diaphragm is assembled into a button battery.
[0072] Next, the battery was charged and discharged at a rate of 0.1C in the range of 3.0V~4.4V. After the third charge to 4.4V, the battery was disassembled, the positive electrode material was taken out, and the electrolyte on its surface was washed off with a solvent (dimethyl carbonate, DMC). After drying, the DSC test was performed according to the method in Part 5 of GB / T 19466.5-2022 Plastic Differential Scanning Calorimetry (DSC), where the heating rate was 2℃ / min, and the decomposition temperature and decomposition heat of the positive electrode material were recorded.
[0073] (3) Electrochemical performance test First, the positive electrode materials in the above-mentioned embodiments and comparative examples are prepared into batteries. Specifically, the positive electrode material, the conductive agent (conductive carbon black) and the binder (polyvinylidene fluoride, PVDF) are mixed in a mass ratio of 97.5:1.5:1, and the uniformly mixed slurry is coated on an aluminum foil and dried, and the positive electrode sheet is obtained after rolling and cutting; the negative electrode active material graphite, the conductive agent (conductive carbon black), the binder (sodium carboxymethyl cellulose, CMC) and the binder (styrene butadiene rubber, SBR) are slurried in deionized water in a mass ratio of 96.5:1:1:1.5. , coat the evenly mixed slurry on copper foil and dry it, and then obtain the negative electrode sheet after rolling and cutting; the diaphragm adopts a composite diaphragm (7μm polyethylene + 3μm ceramic) with a total thickness of 10μm; next, assemble the positive and negative electrode sheets and the diaphragm into a battery with a capacity of about 50Ah, inject 100g of electrolyte, the electrolyte is 1.15M LiPF6 dissolved in a mixed solvent of EC and EMC with a volume ratio of 3:7, and add 1% mass fraction of vinylene carbonate (VC), and then perform high temperature (45°C) hot pressing, and obtain the final battery after capacity separation.
[0074] Cycle performance test: Charge the battery to 4V at 0.5C constant current and constant voltage at 25°C, with a cut-off current of 0.05C; then discharge it to 3.0V at 1C, and obtain the first-week discharge capacity, which is recorded as the battery capacity. Continue the charge and discharge cycle according to the above steps for 100 cycles, and record the discharge capacity after 100 cycles. The capacity retention rate after 100 cycles = (discharge capacity after 100 cycles / first-week discharge capacity) * 100%. In addition, the gram capacity of the positive electrode material is obtained by dividing the battery capacity by the mass of the positive electrode active material (239.62g).
[0075] Battery DCR (Direct Current Resistance) test: At 25°C, first adjust the battery's SOC (State of Charge) to 50%. Next, discharge at a 2C rate for 30 seconds and record the battery's internal resistance.
[0076] (4) Safety performance test The battery in the safety performance test is the same as the battery in the above electrochemical performance test. Specifically, the method of GB38031-2020 is used to place the battery in a hot box, heat it to 130°C, and then keep it warm until the battery has thermal runaway, and record the insulation time when thermal runaway occurs and the highest temperature of thermal runaway.
[0077] The results of all the above tests are shown in Table 1.
[0078] Table 1
[0079] It can be seen from the data in Table 1 that, compared with the positive electrode materials of Comparative Examples 1 to 3, the DSC decomposition temperature of the positive electrode materials in Examples 1 to 3 is significantly increased, and the DSC decomposition heat release is greatly reduced. In addition, the thermal runaway time of the batteries corresponding to Examples 1 to 3 is significantly increased relative to the thermal runaway time of the batteries corresponding to Comparative Examples 1 to 3, and at the same time, the maximum thermal runaway temperature of the batteries corresponding to Examples 1 to 3 is significantly reduced relative to the maximum thermal runaway temperature of the batteries corresponding to Comparative Examples 1 to 3. This shows that in this application, by sequentially forming an oxyhalide and a carbon coating on the surface of a high-nickel ternary material, the carbon coating coats the oxyhalide, which can prevent the oxyhalide from reacting with the electrolyte, thereby ensuring the stability of the oxyhalide, and the oxyhalide can react with the oxygen released by the high-nickel ternary material. The reaction is endothermic, which can effectively reduce the heat generation and increase the oxygen release temperature of the high-nickel ternary material, thereby extending the time for the battery to experience thermal runaway, and can also convert the main reaction of the battery during thermal runaway from an oxidation reaction dominated by the positive electrode to a reduction reaction dominated by the negative electrode, thereby significantly reducing the overall heat generation of the battery, and the maximum temperature of the battery thermal runaway will also be significantly reduced. Moreover, the carbon in the carbon coating can also react with the oxygen released by the high-nickel ternary material, thereby better avoiding the direct reaction of oxygen with the electrolyte to release heat. Therefore, the positive electrode material in this application can better improve the safety performance of the battery.
[0080] From the data in Table 1, it can be seen that compared with the positive electrode materials of Comparative Examples 1 and 2, the gram capacity of the positive electrode materials in Examples 1 to 3 is higher, and the capacity of the corresponding batteries of Examples 1 to 3 is higher, the internal resistance of the batteries is lower, and the capacity retention rate of the batteries after 100 cycles is higher. This shows that in the present application, the oxyhalide is stable at high voltage and has high lithium ion conductivity, which can improve the gram capacity of the positive electrode material, and the carbon coating layer can improve the electronic conductivity of the positive electrode material and reduce the internal resistance of the battery. Therefore, in the positive electrode material of the present application, the combination of the oxyhalide and the carbon coating layer can effectively improve the capacity performance and cycle performance of the battery.
[0081] In Comparative Example 2, only an oxyhalide coating layer is formed on the surface of the high-nickel ternary material, and no carbon coating layer is formed on the surface of the oxyhalide coating layer. The oxyhalide coating layer contacts and reacts with the electrolyte, resulting in poor stability of the oxyhalide coating layer. From the comparison of the data in Comparative Example 2 and Example 1 in Table 1, it can be seen that the gram capacity of the positive electrode material in Comparative Example 2 is low, the internal resistance of the battery is large, and the capacity retention rate after 100 cycles is low, which shows that it is difficult to effectively improve the battery capacity performance and cycle performance only through the oxyhalide coating. In addition, the DSC decomposition temperature of the positive electrode material in Comparative Example 2 is low, the DSC decomposition heat release is high, the corresponding battery has a short thermal runaway time, and the maximum thermal runaway temperature is high, which shows that it is difficult to effectively improve the safety performance of the battery only through the oxyhalide coating.
[0082] From the comparison of the data in Comparative Example 3 and Example 1 in Table 1, it can be seen that in Comparative Example 3, although an oxyhalide coating layer and a carbon coating layer are sequentially formed on the surface of the high-nickel ternary material, so that the gram capacity of the positive electrode material and the battery capacity are at a relatively high level, since the halogen element in the oxyhalide in Comparative Example 3 is fluorine, the oxyhalide cannot react with the oxygen released by the high-nickel ternary material, and therefore cannot reduce the heat generation and increase the oxygen release temperature of the high-nickel ternary material, thereby prolonging the time for thermal runaway of the battery and reducing the maximum temperature of thermal runaway.
[0083] In this application, through the synergistic effect of the oxyhalide coating layer and the carbon coating layer, not only can the gram capacity of the positive electrode material at high voltage (4.4V) be improved, the upper limit voltage of the positive electrode material can be increased, but also the decomposition and oxygenation temperature of the positive electrode material can be increased, and the heat generated by the decomposition and oxygenation can be reduced, because the reaction between oxyhalide and oxygen is an endothermic reaction. Taking LiTaOCl4 as an example, 4LiTaOCl4+O2=2Li2O+4TaOCl3+2Cl2, ΔH>0; 2TaOCl3+1.5O2=Ta2O5+3Cl2, ΔH>0, the above reaction is endothermic, and the decomposition temperature of the positive electrode material can be increased to above 240°C. The thermal runaway is mainly based on the negative electrode reduction reaction, so that the thermal runaway time of the battery can be extended, and the maximum temperature of the thermal runaway can be reduced to below 500°C. The positive electrode material provided in this application can effectively accelerate the application process of high specific energy batteries.
[0084] It should be noted that the positive electrode material embodiments, positive electrode material preparation method embodiments, positive electrode sheet embodiments and battery embodiments provided in the present application belong to the same concept; the technical features in the technical solutions recorded in each embodiment can be combined arbitrarily without conflict.
[0085] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.
Claims
1. A method for preparing a positive electrode material, characterized in that: The method comprises the following steps: S1: uniformly mixing a high-nickel ternary material and a metal halide, performing a first heat treatment under a first protective gas atmosphere to form an oxyhalide on the surface of the high-nickel ternary material, and after cooling, obtaining a ternary material with the oxyhalide coated on the surface; The molecular formula of the oxyhalide is Li a M b O c X d , wherein M includes at least one of Zr, Nb, Ta, W, Ti, La, Yb, In, Er, Sb, Sc, Y, Ho, Hf, Ga, and Dy, X includes at least one of Cl, Br, and I, 0.5≤a≤6, 0.1≤b≤10, 0.1≤c≤2, and 1≤d≤8; S2: uniformly mixing the ternary material coated with oxyhalide, a carbon source and a solvent, performing a second heat treatment under a second protective gas atmosphere to form a carbon coating layer on the surface of the ternary material coated with oxyhalide, and obtaining the positive electrode material after cooling.
2. The method for preparing the positive electrode material according to claim 1, characterized in that: The surface of the high-nickel ternary material includes residual alkali, and the oxyhalide is formed by the reaction of the residual alkali and the metal halide.
3. The method for preparing the positive electrode material according to claim 1 or 2, characterized in that: Step S1 satisfies at least one of the following characteristics: (1) The molecular formula of the high nickel ternary material is LiNi x Co y N z O2, wherein N includes at least one of Mn, Al, Mg, Zr, Ti, W, and B, 0.6≤x≤1.0, 0≤y≤0.2, and 0≤z≤0.4; (2) The metal halide includes at least one of TaCl5, NbCl5, ZrCl4, HfCl4, GaCl3, InCl3, ScCl3, YCl3, YbCl3, YBr3, and ErI3; (3) The mass ratio of the high nickel ternary material to the metal halide is 625:(1-12); (4) The first protective gas includes an inert gas; (5) The temperature of the first heat treatment is 250°C to 500°C; (6) The heating rate of the first heat treatment is 5°C / min~20°C / min; (7) The holding time of the first heat treatment is 4h~10h.
4. The method for preparing the positive electrode material according to claim 1 or 2, characterized in that: Step S2 satisfies at least one of the following characteristics: (1) The carbon source includes at least one of glucose, sucrose, citric acid, ascorbic acid, polyvinyl alcohol, phenolic resin, and starch; (2) The mass of the carbon source is 0.3% to 1.5% of the mass of the ternary material coated with oxyhalide; (3) The solvent includes a polar organic solvent; (4) The second protective gas includes an inert gas; (5) The temperature of the second heat treatment is 150°C to 400°C; (6) The heating rate of the second heat treatment is 5°C / min to 20°C / min; (7) The holding time of the second heat treatment is 4h~10h.
5. A positive electrode material, characterized in that It comprises a core and a first coating layer and a second coating layer which sequentially coat the core; The core includes a high-nickel ternary material; the first coating layer includes an oxyhalide, the molecular formula of the oxyhalide is Li a M b O c X d , wherein M includes at least one of Zr, Nb, Ta, W, Ti, La, Yb, In, Er, Sb, Sc, Y, Ho, Hf, Ga, and Dy, X includes at least one of Cl, Br, and I, 0.5≤a≤6, 0.1≤b≤10, 0.1≤c≤2, and 1≤d≤8; and the second coating layer includes a carbon coating layer.
6. The positive electrode material according to claim 5, characterized in that The lithium in the oxyhalide is derived from the residual alkali on the surface of the high-nickel ternary material; and / or, The molecular formula of the high nickel ternary material is LiNi x Co y N z O2, wherein N includes at least one of Mn, Al, Mg, Zr, Ti, W, and B, 0.6≤x≤1, 0≤y≤0.2, and 0≤z≤0.
4.
7. The positive electrode material according to claim 5 or 6, characterized in that The thickness of the first coating layer is 2nm~30nm; and / or, The thickness of the second coating layer is 1 nm to 16 nm.
8. The positive electrode material according to claim 5 or 6, characterized in that: The mass of the second coating layer is 0.3% to 1.5% of the sum of the masses of the core and the first coating layer.
9. A positive electrode sheet, characterized in that: A positive electrode material prepared by the method for preparing the positive electrode material according to any one of claims 1 to 4 or a positive electrode material according to any one of claims 5 to 8.
10. A battery, characterized in that: Including the positive electrode sheet as described in claim 9.
Citation Information
Patent Citations
Ternary positive material preparation method and ternary positive material
CN107579237A
Lithium battery composite positive electrode material with core-shell structure and preparing method of lithium battery composite positive electrode material
CN108054378A
Carbon-coated ternary material and preparation method thereof
CN108199013A
A preparation method of a carbon-coated ternary positive electrode material and the carbon-coated ternary positive electrode material
CN110429275A
Carbon-coated ternary positive electrode material, preparation method and application thereof
CN113889624A